Dilemmas experienced by government veterinarians when responding professionally to farm animal welfare incidents in Ireland. Issue 1 (6th February 2014) - Devitt, C.; Kelly, P.; Blake, M.; Hanlon, A.; More, S. J.
Abstract : Objectives: This paper identifies the dilemmas experienced by government veterinarians during their investigations of farm animal welfare incidents that involve herd owner social, health, and/or psychological difficulties. The paper builds on exploratory qualitative research into the impact of these difficulties on farm animal welfare. Design: The study used a qualitative research approach. Focus groups were conducted. Setting: In Ireland, an Early Warning System (EWS), which brings together relevant agencies, is in place to identify and prevent farm animal welfare problems before they become critical. This study is concerned with the experiences of government veterinarians who respond to farm animal welfare incidents. Specific focus is on incidents that involve herd owner social/psychological/health‐related difficulties. Participants: In total, n=18 government veterinarians (representing 15 per cent of the population sample), all with a keen interest in farm animal welfare, participated. These were selected on the basis of their interest, experience, and involvement in farm animal welfare. One government veterinarian declined to participate. Four focus groups were conducted with government veterinarians. These took place in the south (S), south‐west (SW), midlands (M), and north‐west region of Ireland (NW). All 16 District Veterinary Offices (DVOs) were represented in the focus groups. Results: The results reveal three professional dilemmas that exist for government veterinarians: (1) defining professional parameters; (2) determining the appropriate response; (3) involvement versus detachment. Participants reported not wanting any additional training. Instead, it was agreed that a formal bridge to social service providers who have the professional capability to respond appropriately and with confidence, was required. Conclusions: Clearly defined guidelines are required for government veterinarians in their encounters with farm animal welfare incidents where there is a complex human component. A coordinated multiagency approach that is flexible enough to meet the needs of individual farm animal welfare cases is required.